Latin America and the Caribbean: a dissertation bibliography, editado por Carl W. Deal (Revista de Biblioteconomia de Brasília, 1979)
DEAL, Carl W. (ed.). Latin America and the Caribbean: a dissertation bibliography. Ann Arbor: University Microfilms International, 1978. 164 p.